Semantic Structure of Noun Units with the General Name "Honesty" (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article analyzes the semantic structure of noun units with the general term "Honesty". In the process of analysis, the meanings of lexemes in the Uzbek language in various speech processes are studied. Semasiology is one of the most important achievements of linguistics. In the process of analyzing semantic structures, noun units with the meaning "Honesty" found in various artistic and scientific sources are studied.